THE IMPACT OF THE DASH AND MEDITERRANEAN DIETS ON BLOOD PRESSURE AND CARDIOVASCULAR RISK FACTORS: A REVIEW OF SCIENTIFIC EVIDENCE AND PRACTICAL IMPLICATIONS - Konrad Strużek,; Agnieszka Kwiatkowska,; Ewelina Mączka,; Wiktor Tracz,; Patrycja Świercz,; Kinga Teper,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka,; Aleksandra Ewa Basak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Hypertension is one of the major risk factors for premature mortality and cardiovascular diseases. Lifestyle modifications, including diet, play a crucial role in its prevention and treatment. The aim of this review was to assess the impact of the DASH diet and the Mediterranean diet (MedDiet) on blood pressure values.Materials and methods: Data from randomized controlled trials (RCTs) and meta-analyses examining the effects of the DASH and MedDiet on systolic (SBP) and diastolic blood pressure (DBP) were analyzed. The review included key studies such as PREMIER, DASH-Sodium, ENCORE, PREDIMED, as well as meta-analyses published up to 2021.Results: The DASH diet was associated with significant reductions in SBP and DBP, particularly when combined with sodium reduction, weight loss, and increased physical activity. The MedDiet also contributed to blood pressure lowering, although the effect was smaller (average reduction in SBP by 1.5 mmHg and in DBP by 0.9 mmHg compared to other diets) and depended on the study population and control group.Conclusions: Both the DASH and Mediterranean diets are effective non-pharmacological strategies for managing hypertension. Their implementation should be supported through counseling, mobile technology, and systemic actions. Further RCTs with sodium intake monitoring are needed to more fully assess the impact of the MedDiet on blood pressure.